MESTIZAJE, VIDA COTIDIANA Y CULTURA MATERIAL UNA MIRADA SOCIOCULTURAL A DOS MATRIMONIOS INTERÉTNICOS EN LA CIUDAD DE CÓRDOBA, SIGLO XVIII - Moreyra, Cecilia Edith (2012)
Cordoba colonial society was deeply hierarchical and stratified, but was also permeable to social mobility, despite attempts segregation, there were profuse and varied relationships between different social groups. In this context, the mixing is presented as a complex social phenomenon that can be approached from different perspectives. In this paper we propose a sociocultural reading, with special emphasis on everyday life and material culture of two marriages between people of different backgrounds socioethnic in the city of Cordoba, Argentina in the eighteenth century. From studies of two selected cases, it is intended, first, to analyze the role played by material objects in the game of social ascent and descent and, secondly, to recover the experience of the subject, premise called “cultural turn” in historical research. The concept of material culture is understood as the permanent relationship between man and objects, which, far from being merely useful, they are also symbolic elements of culture to communicate and express.